C-coordinated O-carboxymethyl chitosan Cu(II) complex exerts antifungal activity by disrupting the cell membrane integrity of Phytophthora capsici Leonian. (1st June 2021) - Ma, Yuzhen; Gao, Kun; Yu, Huahua; Liu, Weixiang; Qin, Yukun; Xing, Ronge; Liu, Song; Li, Pengcheng
Graphical abstract: Highlights: FITC-O-CSLn-Cu was first synthesized to study the antifungal mechanism and could pass through the fungus cell membrane. O-CSLn-Cu led to a negative remodeling model of cell membrane structure. Aquaporin 10 was first cloned in fungi and proved to be a potential molecular target of antimicrobial agents. Abstract: Damage to the cell membrane is an effective method to prevent drug resistance in plant fungal diseases. Here, we proposed a negative remodeling model of the cell membrane structure induced by the C-coordinated O-carboxymethyl chitosan Cu (II) complex (O-CSLn-Cu). FITC-labeled O-CSLn-Cu (FITC-O-CSLn-Cu) was first synthesized via a nucleophilic substitution reaction and confirmed by FT-IR. FITC-labeled O-CSLn-Cu could pass through the fungal cell membrane, as detected by confocal laser scanning microscopy (CLSM) coupled with fluorescein isothiocyanate (FITC)-fluorescence. O-CSLn-Cu treatment led to apparent morphological changes in the membranes of P. capsici Leonian and giant unilamellar vesicles (GUVs) by transmission electron microscopy (TEM). Then, we performed component analysis of the cell membrane from the P. capsici Leonian affected by O-CSLn-Cu with a particular interest in membrane physicochemical properties. Many unsaturated fatty acids (UFAs) and key enzymes promoting UFA synthesis of the cell membrane were downregulated. Similarly, a large number of membrane proteins responsible for substance transport and biochemical reactions were downregulated. Furthermore, O-CSLn-Cu treatments increased plasma membrane permeability with significant leakage of intercellular electrolytes, soluble proteins and sugars, and lipid peroxidation with decreasing membrane fluidity. Finally, aquaporin 10 was proven to be a potential molecular target sensitive to antimicrobial agents according to composition analysis of membrane structure and immunohistochemistry.